Naringinase Immobilized on Modified Banana Peel with Potential Application in the Citrus Industry (2023)
ABSTRACT: Banana peel after chemical ant thermal modification was used as an alternative support to immobilize the commercial enzyme naringinase (Penicillum Decumbens); an immobilization yields greater than 70% was observed at pH 7. The structural characteristics of the support were determined by scanning electron microscopy with elemental analysis, showing the presence of pores and elements such as carbon, oxygen, sulfur, and zinc, while the attachment of the enzyme was concluded by infrared spectroscopy. For the free and immobilized enzyme, the KM and Vmax values were 0.0006 molar and 2000 U, and 0.0003 molar and 1666 U, respectively. The temperatures of the greatest activity for the free was 70°C and for the immobilized enzyme was 50°C, respectively, and the best pH was 4.5 in both cases. It was found that, after the third use, the catalyst maintained 50% of the enzymatic activity. These results seem to suggest the potential of the synthesized material for its application in the debittering of citrus juices.